Emergency Survey and Stability Analysis of a Rainfall-Induced Soil-Rock Mixture Landslide at Chongqing City, China - Zhou, Chang; Ai, Dong; Huang, Wei; Xu, Huiyuan; Ma, Liwen; Chen, Lichuan; Wang, Luqi (Frontiers in Earth Science, 2021)
The stability analysis of the damaged landslide is important for rescue work and emergency operation. This paper investigated a predisposing geological emergence, inducing the factors and deformation processes of the Zhongbao landslide, which happened on 25 July 2020. The stability of the damaged landslide was evaluated by an integrated monitoring system consisting of ground-based radar, unmanned aerial vehicles, airborne Lidar, thermal infrared temperature monitoring, GNSS displacement monitoring, deep displacement monitoring and rainfall monitoring. The strata and weak layer controlled the landslide failure, and topography defined the boundary of the failed rock mass. A continually intensive rainfall caused the deformation and accelerated failure of the landslide. The shallow and steep deposit (Part I) firstly slid at a high velocity, and then pushed the rear part of the landslide (Part II) to deform, forming numerous cracks, which accelerated the rainfall infiltrating into the rock mass. The moisture content increase could decrease the strength of the shale rock with bedding planes. Finally, the rock and soil mass sliding along the weak layer, a barrier dam and a barrier lake were formed. The monitoring and numerical simulation results showed that after the landslide failure, there were still local collapse and deformation occurrence which threatened rescue work and barrier lake excavation, and the stability of the accumulation area gradually decreased as the rainfall increased. Therefore, the barrier dam wasn’t excavated until the accumulation rate gradually stabilized on July 28. Moreover, most of the reactivated deposits still accumulated in the transportation and source areas. Thus, in August, the displacement of the damaged landslide gradually accelerated in a stepwise manner, and responded strongly to rainfall, especially in the accumulation area, so that it was inferred that the damaged landslide could slide again and caused a more threatening and severe failure. The analysis results of the study area can provide references for the failure mechanism of a rainfall-induced landslide and the stability evaluation of a damaged landslide.